Conservation Office and monument, that is, the influence of the office on the preparation and implementation of conservation works - Korpała, Małgorzata (Protection of Cultural Heritage, 2016)
Under the Act of 23 July, 2003 on the Protection and Guardianship of Monuments, employees of historic preservation offices supervise works carried out to historic monuments and sites as well as determine their scope. The scope of works depends on the form of legal protection and it is conditional on the decision pertaining to legal protection, i.e. listing a property or site in the register or municipal/communal record of historic monuments and sites; providing area-wide protection: defining historic preservation area in a local zoning plan. Members of staff of historic preservation offices are responsible for assessing documents pertaining to renovation, restoration, and conservation works carried out to monuments and sites as well as make administrative decisions on all actions, regardless of the level on which they are taken: issuing conservation guidelines, permits for conducting research on historic monuments and sites, making decisions on commencing conservation works, supervising the works until their completion. Quality of works carried out to historic monuments and sites depends on individual experience and skills that the members of staff of historic preservation offices demonstrate. The higher the rank of a monument or site, the heavier responsibility historic preservation offices shoulder.